Thoracic squeezing on airway secretion and respiratory parameters in mechanically ventilated patients: An interventional study - P Thenmozhi; P Dineshkumar; G Bhuvaneswari; T Mary Minolin; S Tamilselvi (Journal of Education and Health Promotion)
BACKGROUND: The most common method for preventing ventilator-associated pneumonia is maintaining airway clearance for efficient gas exchange, achieved by removing secretion through endotracheal or tracheal suctioning. Clearing the airway can be effectively achieved through various techniques, including thoracic squeezing. Thus, this study aimed to determine the effectiveness of thoracic squeezing on airway clearance, and respiratory parameters among mechanically ventilated patients. MATERIALS AND METHODS: A true experimental study was conducted with 60 mechanically ventilated patients who met the inclusion criteria in the ICUs and were randomly assigned to the study group (n = 30) and the control group (n = 30). Pre-intervention assessments of airway secretion, oxygen saturation, respiratory rate, and heart rate were measured before suctioning for both groups. Thoracic squeezing was administered to the study group 5 minutes before suctioning, while the control group received the hospital’s routine care practices. Post-intervention assessments 1 and 2 were measured immediately and 15 minutes after suctioning, and the same process continued for three days in both groups. RESULTS: The mean scores of airway secretion, respiratory rate, oxygen saturation, and heart rate from the pre- and post-intervention assessments 1 and 2 were compared using repeated measures ANOVA. The results revealed a high level of statistical significance (P < 0.001) for airway secretion and oxygen saturation and statistical significance (P < 0.05) for respiratory rate. However, no significant changes were observed in heart rate. An unpaired t-test revealed that participants in the study group were significantly (P < 0.001) more effective in airway secretion and oxygen saturation than in the control group participants. CONCLUSION: The current study’s findings concluded that thoracic squeezing before endotracheal and tracheal suctioning enhances secretion removal, oxygen saturation, and respiratory rate without significant changes in heart rate among mechanically ventilated patients. Its notable influence could provide policymakers with valuable insights to make well-informed decisions, focused on improving healthcare systems and outcomes, especially within intensive care units.